Intracerebral hemorrhage: update and future directions - ROCHA, Eva; ROUANET, Carolina; REGES, Danyelle; GAGLIARDI, Vivian; SINGHAL, Aneesh Bhim; SILVA, Gisele Sampaio (Arquivos de Neuro-Psiquiatria, 2020)
Intracerebral hemorrhage (ICH), defined as bleeding into the brain parenchyma, is a significant public health issue. Although it accounts for only 10 to 15% of strokes, it is associated with the highest morbidity and mortality rates. Despite advances in the field of stroke and neurocritical care, the principles of acute management have fundamentally remained the same over many years. The main treatment strategies include aggressive blood pressure control, early hemostasis, reversal of coagulopathies, clot evacuation through open surgical or minimally invasive surgical techniques, and the management of raised intracranial pressure.
Keywords: Cerebral Hemorrhage; Stroke; Critical Care